2022
DOI: 10.1021/acsomega.2c02021
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized MOF as a Sensitive Spectroscopic Probe for Hg2+, Co2+, and Al3+ Ions Detection in Aqueous Media

Abstract: A modified metal–organic framework (MOF) named Al-MIL-53-N=SA-Br was synthesized via a Schiff-base reaction between the MOFs (Al-MIL-53-NH 2 ) and 5-bromo salicylaldehyde. The robust functionalized Al-MIL-53-N=SA-Br was used as a novel spectrophotometric sensor for detecting Hg 2+ , Co 2+ , and Al 3+ ions. In a wide range of concentrations, the absorption spectral intensity of Al-MIL-53-N=SA-Br increased linearly upon i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…3d). Compared with several sensors previously used for the determination of Hg 2+ , 21–30 the detection limit of the JXUST-28 sensor was found to be at a low level (Table S5, ESI†).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…3d). Compared with several sensors previously used for the determination of Hg 2+ , 21–30 the detection limit of the JXUST-28 sensor was found to be at a low level (Table S5, ESI†).…”
Section: Resultsmentioning
confidence: 87%
“…20 The stable MOF materials are rich in pore surfaces and functional sites, which can be used for the detection and removal of mercury ions from wastewater. [21][22][23][24][25][26][27][28] For example, Wang and his colleagues designed a dual functional material (NH 2 MIL-53(Al)) for the adsorption and removal of Hg 2+ ions with a limit of detection (LOD) of 0.15 μM. 29 Yang and coworkers report a Sm III -MOF derived from 2-aminoterephthalic acid for the removal and detection of Hg 2+ ions, which has excellent selectivity and high sensitivity with a wide linear range of 0.6-300 μM and a LOD of 0.87 μM.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16] More recently, metal-organic frameworks (MOFs) with geometrically well-defined structures have attracted substantial attention in the fields of biomedicine and biosensors. [17][18][19][20][21] Besides, zeolitic imidazolate framework-90, derived from Zn 2+ and an imidazole-2-carboxaldehyde (2-ICA) ligand, has been widely used in ATP imaging, owing to its distinct chemical stability and excellent biocompatibility, as well as mitochondria-targeting ability. 17 Moreover, the covalent functionalization of the free aldehyde groups in the ZIF-90 framework is easily achieved, supporting its role as a fluorometric sensor.…”
Section: Introductionmentioning
confidence: 99%
“…12 Fluorescent probes have recently received extensive attention from academia and industry 13,14 because these sensors can quantitatively detect Hg 2+ 15,16 with good selectivity, high sensitivity, and low detection limit and are simple to operate at relatively low cost. 17–19 It has been reported that fluorescence sensors have been used to study the biochemical processes related to Hg 2+ in organisms, 20,21 which has promoted the development of non-invasive approaches. 22,23 Recently, Chung et al 24 integrated platinum( ii ) terpyridine and dithiaazacrown, exhibiting a metal-to-ligand charge transfer transition and an internal charge transfer transition to realize a dual channel sensing mode, which could detect low concentrations of Hg 2+ .…”
Section: Introductionmentioning
confidence: 99%